Meningkatkan Kemampuan Berpikir Kritis Siswa Melalui Penerapan Model Pembelajaran Think Pair Share - Olo, Maria Regina; Simarmata, Justin Eduardo; Mamoh, Oktovianus (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
The problem in this study is the low ability of students' critical thinking so that students are not able to solve math problems related to critical thinking skills. To overcome this problem, the think pair share learning model is applied. This study aims to improve the critical thinking skills of grade VIII junior high school students through the application of the think pair share learning model. This type of research is classroom action research. The results showed that there was an increase in critical thinking skills through the application of the Think Pair Share learning model. The increase in critical thinking skills is seen in the average of each indicator and the percentage of achievement for each indicator. The average critical thinking ability on indicator (1) in cycle I was 2.42, an increase of 2.54, indicator (2) of 1.51, an increase of 1.61, indicator (3) of 2.10, an increase of 2, 34, indicator (4) was 1.23 to 1.51 and the percentage of achievement, namely indicator (1) was 80.66% to 84.66%, indicator (2) was 75.50% to 81.00%, indicator ( 3) by 70.00% to 78.00% and indicator (4) by 65.50% to 75.50%.